2019
DOI: 10.31234/osf.io/f8czn
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Internalizing Symptoms and Social Support Among Kenyan Adolescents: A Network Analysis

Abstract: Internalizing symptoms are common and debilitating among adolescents. Network analysis, which models associations among psychopathology, risk factors, and protective factors, may help clarify relationships between social support and internalizing symptoms, including within understudied cultural groups. We performed network analyses of 1) depressive and anxiety symptoms, 2) social support, and 3) all three measures among 658 Kenyan adolescents. In the internalizing symptoms network, worry, nervousness, and feel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…This study is, to the best of our knowledge, the first attempt of its kind to combine wellbeing elements and psychopathology in a network approach with SSA youths. The recent network research of child and adolescent psychopathology has been conducted almost exclusively with Western adolescent populations [ 52 , 57 60 ] with only a few studies in the Global South [ 61 – 63 ]. More research focused on SSA youths is necessary since there are scientific benefits of cross-cultural research and culture affects psychopathology and psychological wellbeing.…”
Section: Discussionmentioning
confidence: 99%
“…This study is, to the best of our knowledge, the first attempt of its kind to combine wellbeing elements and psychopathology in a network approach with SSA youths. The recent network research of child and adolescent psychopathology has been conducted almost exclusively with Western adolescent populations [ 52 , 57 60 ] with only a few studies in the Global South [ 61 – 63 ]. More research focused on SSA youths is necessary since there are scientific benefits of cross-cultural research and culture affects psychopathology and psychological wellbeing.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, peer-reported aggressive behaviours in school have been associated with depression 25 . Network analysis revealed that the lack of social support, especially the support from friends, correlates with adolescents’ internalizing symptoms, including depression 16 .…”
Section: Discussionmentioning
confidence: 99%
“…We adopted the “goldbricker” procedure in the R package of “network tools” to investigate the problematic topological overlap between variables. If two items are topologically connected with the other items without differential associations, it means these two items are the same, and one of them can be removed, or it is plausible to combine those two via principal component analysis (PCA) 16 .…”
Section: Methodsmentioning
confidence: 99%
“…This study is, to the best of our knowledge, the rst attempt of its kind to combine wellbeing elements and psychopathology in a network approach with SSA youths. The recent network research of child and adolescent psychopathology has been conducted almost exclusively with Western adolescent populations [49][50][51][52][53] with only a few studies in the Global South [54][55][56]. Research focused on SSA youths is necessary since there are scienti c bene ts of cross-cultural research and culture affects psychopathology and psychological wellbeing.…”
Section: Discussionmentioning
confidence: 99%